(untitled) (Vegueta: Anuario de la Facultad de Geografía e Historia, 2017)
During the Late Middle Ages, alchemy attracted the interest of many eminent scholars, yet alchemy’s constant failure to produce the philosopher’s stone veiled the art with a cloak of scorn. In this article, I examine the cases of Roger Bacon and of John of Rupescissa, both of whom entwined alchemy with philosophy and theology, portraying the hermetic art as a salutary practice for humanity and the Church. Therefore, my scrutiny of their works aims to demonstrate alchemy’s desire, albeit somewhat implicit, for recognition and legitimization.